Structures of Native-like Nucleosomes: One Step Closer toward Understanding the Structure and Function of Chromatin. Issue 6 (19th March 2021) - Bai, Yawen; Zhou, Bing-Rui
Abstract: Genomic DNA in eukaryotes is organized into chromatin through association with core histone proteins to form nucleosomes. To understand the structure and function of chromatin, we must determine the structures of nucleosomes containing native DNA sequences. However, to date, our knowledge of nucleosome structures is mainly based on the crystallographic studies of the nucleosomes containing non-native DNA sequences. Here, we discuss the technical issues related to the determination of the nucleosome structures and review the few structural studies on native-like nucleosomes. We show how an antibody fragment-aided single-particle cryo-EM can be a useful method to determine the structures of nucleosomes containing genomic DNA. Finally, we provide a perspective for future structural studies of some native-like nucleosomes that play critical roles in chromatin functions. Graphical Abstract: Unlabelled Image Highlights: Nucleosome core particles consist of 145 bp DNA. scFv-aided cryo-EM approach allows structural determination of native-like nucleosomes.